2010
DOI: 10.4137/ijis.s4698
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Role of Anopheles Mosquitoes in Malaria Transmission Along Badagry Axis of Lagos Lagoon, Lagos, Nigeria

Abstract: Three communities along Badagry axis of the Lagos lagoon were sampled for indoor resting Anopheles mosquitoes in order to determine their species composition, relative abundance, density and contribution to malaria transmission in the coastal ecosystem. A total of 1938 adult female Anopheles mosquitoes collected from 2005 to 2007 constituted three species viz Anopheles gambiae, An melas and An. nili. The Polymerase Chain Reaction (PCR)–-based tests indicated that more than three-fourth of the An. gambiae s.l (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…However, the sporozoite infection rates that were obtained were significantly higher than the ones previously reported, 6.70% and 6.30% in 2001 and 2002 respectively, at Igbo-Ora, Oyo State in South-Western Nigeria (Noutcha and Anumdu, 2009), as well as at Badagry Axis of Lagos Lagoon, Lagos State, Nigeria (Oyewole et al, 2010). However, Obembe and Awopetu (2014) has reported similarly high P. falciparum sporozoite rates in the study areas.…”
Section: Discussioncontrasting
confidence: 51%
“…However, the sporozoite infection rates that were obtained were significantly higher than the ones previously reported, 6.70% and 6.30% in 2001 and 2002 respectively, at Igbo-Ora, Oyo State in South-Western Nigeria (Noutcha and Anumdu, 2009), as well as at Badagry Axis of Lagos Lagoon, Lagos State, Nigeria (Oyewole et al, 2010). However, Obembe and Awopetu (2014) has reported similarly high P. falciparum sporozoite rates in the study areas.…”
Section: Discussioncontrasting
confidence: 51%
“…For instance, the P. falciparum sporozoite infection rates for A. gambiae that were recorded at Igbo-Ora in 2001 and 2002, a rural community of Oyo State in south-west Nigeria, were 6.70% and 6.30% respectively (Noutcha and Anumdu, 2009). Along Badagry Axis of Lagos Lagoon, Lagos, Nigeria, P. falciparum sporozoite infection rates of 4.8% and 6.5% for A. gambiae s.s and A. melas respectively were reported (Oyewole et al, 2010). Oduola et al (2012) reported that P. falciparum sporozoite infection rates of A. gambiae s.s. in six rural communities of Oyo State, Southwestern Nigeria, varied between 1.9% and 3.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The An. gambiae complex is not the only vector in the field [6,8]. Targeting only this species by whatever method is nonsense.…”
Section: Malaria Parasitesmentioning
confidence: 99%
“…Meanwhile, the distribution of the molecular M (Mopti) and S (Savannah) forms of An. gambiae s.s is still being determined for much of the West African regions [6,8]. The malaria problem in sub-Saharan Africa represents a peculiar case because the vectoral system is the most complex anywhere.…”
Section: Malaria Parasitesmentioning
confidence: 99%
See 1 more Smart Citation